Method for producing cured film and use thereof
By using hydrogenated olefin compounds of specific structural units and subjecting electron beam or ion irradiation, the problem of insufficient density and hardness of the photoresist layer is solved, and a high-density and hardness carbide film is achieved, and the corrosion resistance and protection performance of the photoresist layer are improved.
Patent Information
- Application Number
- JP2024010425
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-10
- Filing Date
- 2024-01-26
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2040-04-24
AI Technical Summary
In the prior art, when manufacturing semiconductor chips, the density and hardness of the photoresist layer are insufficient, resulting in poor accuracy and corrosion resistance of the photoresist pattern, and the photoresist is prone to oxidation and loss.
A hydrogenated olefin compound containing a specific structural unit is used as the base coating and converted into a high density, hardness-enhanced carbide film by electron beam or ion irradiation.
A high-density and high-hardness carbide film is achieved, the corrosion resistance and protection performance of the photoresist layer are improved, and the oxidation and loss of the photoresist are avoided.
Smart Images

Figure 0007657988000001 
Figure 0007657988000002 
Figure 0007657988000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a cured film and uses thereof. [Background technology]
[0002] In the manufacturing process of semiconductors, microfabrication is generally performed by lithography technology using photoresist (hereinafter, simply referred to as resist). The microfabrication process includes forming a thin photoresist layer on a semiconductor substrate such as a silicon wafer, covering the layer with a mask pattern corresponding to the pattern of the target device, exposing the layer to active light such as ultraviolet light through the mask pattern, obtaining a photoresist pattern by developing the exposed layer, and etching the substrate using the obtained photoresist pattern as a protective film, thereby forming fine irregularities corresponding to the above-mentioned pattern. In semiconductor manufacturing, efforts are underway to reduce the area of IC chips by increasing the number of transistors per unit area, thereby continually reducing the cost per unit transistor. This is achieved by shortening the wavelength of the ultraviolet light irradiated onto the photoresist, thereby attempting to achieve finer processing.
[0003] When using ultraviolet light with a single wavelength (e.g., 248 nm KrF light source), the problem of reduced dimensional accuracy of the resist pattern occurs due to the effect of standing waves. In order to solve this problem, a method of providing a bottom anti-reflection film has been widely studied. The characteristics required for such a bottom anti-reflection film include a high anti-reflection effect. To achieve even finer processing, methods using ArF light sources (193 nm) and EUV (13 nm) are being widely considered. In this case, if the resist film is too thick, the resist pattern is likely to collapse or develop residues are likely to be generated. Therefore, there is a problem that the resist alone does not provide sufficient protective film function. Therefore, a method known as multi-layering has become common, in which a new protective film is created under the photoresist, the photoresist pattern is transferred to the lower film, and the substrate is etched using this lower film as a protective film.
[0004] There are various types of multi-layer protective films, and an amorphous carbon film is sometimes used as the protective film.
[0005] One method for improving the function of the protective carbon film by applying a solution and baking it is to apply a carbon film that can withstand baking at temperatures above 450° C., which is a common baking temperature, and bake it at, for example, 600° C. In addition, the function of the protective film can be improved by increasing the carbon concentration in the solid matter of the carbon film formation solution, but this generally involves a trade-off with other performance properties such as solubility.
[0006] In this technical situation, Patent Document 1 examines a technology for producing a cured film by irradiating a conductive polymer precursor such as polythiophene with plasma to polymerize it, in order to obtain a film with excellent heat resistance and moisture resistance. Patent Document 2 describes the synthesis of a compound in which monocyclic hydrocarbons are linked in order to achieve film-formability, solubility in solvents, and heat resistance, and provides the use of the compound as an underlayer film, but makes no mention of the use of plasma irradiation, electron beam, or ion irradiation in the film formation process. Patent Document 3 examines a method for forming a resist underlayer film having excellent etching resistance. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 5746670 [Patent Document 2] WO2018 / 115043 International Publication [Patent Document 3] JP 2016-206676 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present inventors have recognized that there are one or more problems that still require improvement, including, for example: The density of the cured film is insufficient; the hardness of the cured film is insufficient; the intensity ratio of Raman spectroscopy R=I D / I G a cured film having a viscosity of 0.35 to 0.9 cannot be obtained; a cured film having a hard structure such as a diamond-like carbon structure cannot be obtained; the etch resistance of the film is insufficient; an insulating cured film cannot be obtained; the solubility of the solute in the solvent in the composition used is insufficient; the coatability of the composition is low; the film oxidizes during plasma or electron beam treatment; or the solid components of the film are scattered excessively during plasma or electron beam treatment, resulting in the film being lost. The inventors of the present invention have focused on the possibility that the function of a carbon film as a protective film in a lithography process can be improved by increasing the film density. Therefore, they thought that it would be useful to create a carbon film with a large amount of sp3 carbon, the same as diamond. At the same time, they also thought that it would be useful for such components to have high solubility. As a result of their investigations, the inventors of the present application have discovered a production method in which a film containing a large amount of sp3 carbon and a high density can be obtained by treating a film formed from a specific hydrocarbon-containing compound with energy such as plasma or an electron beam.
[0009] The present invention has been made based on the above-mentioned technical background, and provides a method of: (1) applying (i) a composition above a substrate; (2) (i) forming a hydrocarbon-containing film from the composition; and (3) irradiating the hydrocarbon-containing film with plasma, an electron beam, and / or ions to form a cured film. [Means for solving the problem]
[0010] The method for producing a cured film according to the present invention comprises the following steps: (1) applying a composition (i) above a substrate; (2)(i) forming a hydrocarbon-containing film from the composition; and (3) Irradiating the hydrocarbon-containing film with an electron beam and / or ions to form a hardened film; provided that (i) the composition comprises (A) a hydrocarbon-containing compound, and (B) a solvent; The (A) hydrocarbon-containing compound comprises a structural unit (A1) represented by the following formula (A1): [ka] Here, Ar 11 is R 11 C substituted or not substituted 6-60 (where Ar 11 does not contain fused aromatic rings); R 11 is C 1-20 linear, branched or cyclic alkyl, amino, or alkylamino; R 12 is I, Br or CN; p 11 is a number between 0 and 5, and p 12 is a number between 0 and 1, and q 11 is a number between 0 and 5, and q 12 is a number between 0 and 1, and r 11 is a number between 0 and 5, and s 11 is a number between 0 and 5; p 11 , q 11 and r 11 cannot be zero simultaneously within one unit, When irradiating with an electron beam in step (3), Acceleration voltage is 2 kV to 200 kV, or The irradiation dose is 100kGy to 5,000kGy. When ions are irradiated in the step (3), The elemental species of the ions to be irradiated is hydrogen, boron, carbon, nitrogen, a rare gas, or a mixture of any of these, Acceleration voltage is 3 to 1000 kV, or The irradiation dose is 10 13 ~10 18 ion / cm 2 It is.
[0011] The present invention also provides a method for producing a resist layer above the cured film. The present invention also provides a method for exposing and developing the resist layer to produce a resist pattern. The present invention also provides a method for producing a device comprising any one of the above methods. Effect of the Invention
[0012] By using the method for producing a cured film of the present invention, one or more of the following effects can be expected. A cured film with high film density can be obtained; A cured film with high film hardness can be obtained; The intensity ratio of Raman spectroscopy R = I D / I G a cured film having a molecular weight of 0.35 to 0.9 can be obtained; a cured film having a diamond-like carbon structure can be obtained; a film with high etch resistance can be obtained; an insulating cured film can be obtained; the solute in the composition used has good solubility in the solvent; the composition has high coatability; the film can be prevented from being oxidized during plasma or electron beam treatment; and the film can be prevented from being lost due to excessive scattering of solid components of the film during plasma or electron beam treatment. Because the cured film of the present invention can have these advantageous properties, it can be applied to the manufacturing process of fine devices, and is preferably applied to the manufacture of semiconductors, and more preferably to the manufacture of DRAMs and 3D NAND. The cured film of the present invention is also effective as SOC (Spin on carbon) for hard masks and core SOC. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The embodiment of the present invention will be described in detail below.
[0014] definition In this specification, unless otherwise specifically stated, the definitions and examples set forth in this paragraph shall be followed. The singular includes the plural, and "a" or "the" means "at least one." An element of a concept may be expressed by a plurality of species, and when an amount thereof (e.g., mass % or mole %) is stated, the amount refers to the sum of the plurality of species. "And / or" includes all combinations of elements as well as their use alone. When a numerical range is indicated using "~" or "-", it includes both endpoints and the units are the same. For example, 5 to 25 mol % means 5 mol % or more and 25 mol % or less. "C x-y ", "C x ~C y " and "C x " refers to the number of carbons in a molecule or substituent. For example, C 1~6 Alkyl refers to an alkyl chain having from 1 to 6 carbons (methyl, ethyl, propyl, butyl, pentyl, hexyl, etc.). When a polymer has multiple types of repeating units, these repeating units are copolymerized. These copolymerizations may be alternating copolymerization, random copolymerization, block copolymerization, graft copolymerization, or a mixture of these. When polymers or resins are shown by structural formulas, the n or m in parentheses indicates the number of repeats. Temperature is measured in degrees Celsius. For example, 20 degrees means 20 degrees Celsius. The additive refers to a compound having that function (for example, in the case of a base generator, it is a compound that generates a base). There may be an embodiment in which the compound is dissolved or dispersed in a solvent and added to the composition. In one embodiment of the present invention, such a solvent is preferably contained in the composition according to the present invention as the (B) solvent or other component.
[0015] The entire contents of International Publication No. WO2018 / 115043, International Patent Application No. PCT / EP2018 / 079621 filed October 30, 2018, International Patent Application No. PCT / EP2018 / 085147 filed December 17, 2018, and European Patent Application No. 18199921.3 filed October 5, 2018 are hereby incorporated by reference.
[0016] composition The method for producing a cured film according to the present invention comprises the following steps: (1) applying (i) a composition over a substrate; (2) forming a hydrocarbon-containing film from the (i) composition; and (3) irradiating the hydrocarbon-containing film with plasma, electron beam and / or ions to form a cured film. The (i) composition comprises (A) a hydrocarbon-containing compound and (B) a solvent, and the (A) hydrocarbon-containing compound comprises a structural unit (A1) represented by the formula (A1) described below. The (A) hydrocarbon-containing compound is sufficient as long as it contains the structural unit (A1), and it is permitted to contain other structural units. When the (A) hydrocarbon-containing compound contains other structural units and is a polymer, it is a preferred embodiment that the structural unit (A1) and the other structural units are copolymerized. In a preferred embodiment of the present invention, the (A) hydrocarbon-containing compound is substantially composed of only the structural unit (A1). However, modification of the terminals is permitted. Here, the hydrocarbon-containing film is preferably a resist underlayer film, more preferably a BARC (bottom antireflective coating) or SOC, and further preferably an SOC. As an embodiment of the present invention, there is an SOC for a hard mask and an SOC for a core material.
[0017] (A) Hydrocarbon-containing compounds The (A) hydrocarbon-containing compound according to the present invention comprises a structural unit (A1) represented by the following formula (A1). [ka]
[0018] Ar 11 is R 11 C substituted or not substituted 6-60 where Ar 11 does not contain a condensed aromatic ring. 11 9,9-diphenylfluorene, 9-phenylfluorene, phenyl, C 6-60 Linear polyphenylene and C 6-60 branched polyphenylenes, each of which is independently R 11 may or may not be substituted. R 11 is C 1-20 R is a straight chain, branched or cyclic alkyl, amino or alkylamino. 11 is preferably C 1-10 R is a straight-chain, branched or cyclic alkyl or alkylamino. 11 is more preferably C 1-3 Straight chain alkyl, C 1-3 It is branched alkyl, cyclopentyl, cyclohexyl or dimethylamino. (A) When the hydrocarbon-containing compound has a plurality of structural units (A1), R 11 Ar is used as a linker. 11 They may be bonded to each other via an intervening bond. 11 Replace R 11 may be one or more; preferably, it is one. In one structural unit (A1), a group enclosed in brackets (e.g., p 11 (group enclosed in brackets with R 11 In this case, the group may be bonded to Ar 11 R 11 acts as a linker to bind. Although not intended to limit the present invention and is beyond the scope of the present invention, 11 In the case where the monomer contains naphthyl (for example, naphthol), it is considered to be disadvantageous since it is easily oxidized in the process of the present invention and the reconstruction of the cured film by irradiation with plasma, electron beam and / or ions is difficult to proceed.
[0019] R12 is I, Br or CN; preferably I or Br, and more preferably I. p 11 is a number from 0 to 5. In one embodiment of the present invention, the (A) hydrocarbon-containing compound may have only one each of two types of (A1) as a constituent. 11 Both are phenyl, and one is Ar 11 Related to p 11 = 1, and the other Ar 11 Related to p 11 = 2. In this case, p 11 = 1.5. In this specification, the same applies to numbers unless otherwise specified. p 11 is preferably 0, 1, 2 or 3; more preferably 0, 1 or 2; and even more preferably 1. 11 =0 is also a preferred embodiment of the present invention. p 12 is a number from 0 to 1; preferably 0 or 1; and more preferably 1. q 11 is a number from 0 to 5; preferably 0, 1, 2 or 3; more preferably 0, 1 or 2; and even more preferably 1. 11 =0 is also a preferred embodiment of the present invention. q 12 is a number from 0 to 1; preferably 0 or 1; and more preferably 1. r 11 is a number from 0 to 5; preferably 0, 1, 2 or 3; more preferably 0, 1 or 2; and even more preferably 1. 11 =0 is also a preferred embodiment of the present invention. s 11 is a number from 0 to 5; preferably 0, 1, 2 or 3; more preferably 0, 1 or 2; and even more preferably 1. 11 =0 is also a preferred embodiment of the present invention. p 11 , q 11 and r 11 are never simultaneously 0 within a single unit.
[0020] More specifically, the structural unit (A1) according to the present invention may be a structural unit (A1-1), (A1-2) and / or (A1-3) represented by the following formula (A1-1), (A1-2) and / or (A1-3), each of which will be described later. In a preferred embodiment of the present invention, the structural unit (A1) is the structural unit (A1-1).
[0021] The structural unit (A1-1) is represented by the formula (A1-1). [ka]
[0022] Ar 21 is C 6-50 Ar is an aromatic hydrocarbon of the formula: 21 When is phenyl, the solubility of the (A) hydrocarbon-containing compound in a solvent can be ensured, and advantageous effects such as the ability to form a thick film can be expected. R 21 , R 22 and R 23 are each independently C 6-50 is a single bond bonded to an aromatic hydrocarbon, hydrogen, or other structural unit; preferably a single bond bonded to a phenyl, hydrogen, or other structural unit; more preferably a single bond bonded to a phenyl or other structural unit; and even more preferably a phenyl. n 21 is an integer of 0 or 1; preferably 0. Ar 21 , R 21 , R 22 and R 23 does not contain fused aromatic rings. R 12 , p 11 , p 12 , q 11 , q 12 , r 11 and s 11 The definitions and preferred examples of are independently the same as above.
[0023] Although not intended to limit the present invention, specific examples of the (A) hydrocarbon-containing compound having the structural unit (A1-1) include the following. [ka]
[0024] In a further preferred embodiment of the present invention, the structural unit (A1-1) is the structural unit (A1-1-1). The structural unit (A1-1-1) is represented by formula (A1-1-1). [ka] p 11 , p 12 , q 11 , q 12 , r 11 and s 11 The definitions and preferred examples of are the same as above, provided that 1≦p 11 +q 11 +r 11 Satisfying ≦4.
[0025] The structural unit (A1-2) is represented by the formula (A1-2). [ka] L 31 and L 32 each independently represents a single bond or phenylene; preferably a single bond. n 31 , n 32 , m 31 and m 32 are each independently a number from 0 to 6; preferably an integer from 0 to 3. 31 +n 32 In a preferred embodiment, L = 5 or 6. 31 When is a single bond, m 31 = 1. 32 When is a single bond, m 32 =1. R 12 , p 11 , p 12 , q 11 , q12 , r 11 and s 11 The definitions and preferred examples of are independently the same as above.
[0026] Although not intended to limit the present invention, specific examples of the (A) hydrocarbon-containing compound having the structural unit (A1-2) include the following. [ka]
[0027] The structural unit (A1-3) is represented by the formula (A1-3). [ka] Ar 41 is C 6-50 is an aromatic hydrocarbon of the formula: preferably phenyl. R 41 and R 42 are each independently C 1-10 alkyl; preferably linear C 1-6 It is an alkyl. R 41 and R 42 may form a hydrocarbon ring; preferably forms a saturated hydrocarbon ring. *The carbon atom at position 41 is a quaternary carbon atom. L 41 is C 6-50 or a single bond bonding to another structural unit; preferably a single bond bonding to a phenylene or other structural unit; and more preferably a single bond bonding to another structural unit. R 12 , p 11 , p 12 , q 11 , q 12 , r 11 and s 11 The definitions and preferred examples of are the same as those described above.
[0028] Although not intended to limit the present invention, specific examples of the (A) hydrocarbon-containing compound having the structural unit (A1-3) include the following. [ka]
[0029] In a preferred embodiment of the present invention, when the (A) hydrocarbon-containing compound according to the present invention is a polymer, the amount of the aldehyde derivative used when synthesizing the (A) hydrocarbon-containing compound is preferably 0 to 30 mol % (more preferably 0 to 15 mol %, even more preferably 0 to 5 mol %, and even more preferably 0 mol %) based on the sum of all elements used in the synthesis. An example of the aldehyde derivative is formaldehyde. In one preferred embodiment of the present invention, a ketone derivative is used instead of an aldehyde derivative. The polymer thus synthesized may be characterized by having no or few secondary and tertiary carbon atoms in the main chain. In a preferred embodiment of the present invention, the polymer has substantially no secondary and tertiary carbon atoms in its main chain. Without being bound by theory, this is expected to ensure the solubility of the polymer while improving the heat resistance of the film formed. However, it is acceptable for the polymer to have secondary and tertiary carbon atoms at its terminal, as in terminal modification.
[0030] In one embodiment of the present invention, the molecular weight of the (A) hydrocarbon-containing compound is 500 to 6,000, and more preferably 500 to 4,000. When the (A) hydrocarbon-containing compound is a polymer, the molecular weight is the weight average molecular weight (Mw). In the present invention, Mw can be measured by gel permeation chromatography (GPC). In this measurement, a preferred example is to use a GPC column at 40 degrees Celsius, an elution solvent of tetrahydrofuran at 0.6 mL / min, and monodisperse polystyrene as the standard. The same applies hereinafter. (i) Based on the composition, the amount of (A) the hydrocarbon-containing compound is preferably 2 to 30 mass %, more preferably 5 to 30 mass %, even more preferably 5 to 25 mass %, and still more preferably 10 to 25 mass %.
[0031] (B) Solvent The composition (i) according to the present invention comprises a solvent (B). The solvent (B) is not particularly limited as long as it can dissolve each of the components to be blended. The solvent (B) preferably comprises an organic solvent, and more preferably the organic solvent comprises a hydrocarbon solvent, an ether solvent, an ester solvent, an alcohol solvent, a ketone solvent, or a mixture thereof.
[0032] Specific examples of the solvent (B) include water, n-pentane, i-pentane, n-hexane, i-hexane, n-heptane, i-heptane, 2,2,4-trimethylpentane, n-octane, i-octane, cyclohexane, methylcyclohexane, benzene, toluene, xylene, ethylbenzene, trimethylbenzene, methylethylbenzene, n-propylbenzene, i-propylbenzene, diethylbenzene, i-butylbenzene, triethylbenzene, di-i-propylbenzene, n-amylnaphthalene, trimethylbenzene, methanol, and ethanol. , n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, t-butanol, n-pentanol, i-pentanol, 2-methylbutanol, sec-pentanol, t-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, sec-hexanol, 2-ethylbutanol, sec-heptanol, heptanol-3, n-octanol, 2-ethylhexanol, sec-octanol, n-nonyl alcohol, 2,6-dimethylheptanol-4, n-decanol, sec- Undecyl alcohol, trimethylnonyl alcohol, sec-tetradecyl alcohol, sec-heptadecyl alcohol, phenol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, phenylmethylcarbinol, diacetone alcohol, cresol, ethylene glycol, propylene glycol, 1,3-butylene glycol, pentanediol-2,4, 2-methylpentanediol-2,4, hexanediol-2,5, heptanediol-2,4, 2-ethylhexanediol All-1,3, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, glycerin, acetone, methyl ethyl ketone, methyl-n-propyl ketone, methyl-n-butyl ketone, diethyl ketone, methyl-i-butyl ketone, methyl-n-pentyl ketone, ethyl-n-butyl ketone, methyl-n-hexyl ketone, di-i-butyl ketone, trimethylnonanone, cyclohexanone, cyclopentanone, methylcyclohexanone, 2,4-pentanedione, acetonylacetone, diacetone alcohol,Acetophenone, fenchone, ethyl ether, i-propyl ether, n-butyl ether (di-n-butyl ether, DBE), n-hexyl ether, 2-ethylhexyl ether, ethylene oxide, 1,2-propylene oxide, dioxolane, 4-methyldioxolane, dioxane, dimethyldioxane, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol diethyl ether, ethylene glycol mono-n-butyl ether, ethylene glycol mono-n-hexyl ether, ethylene glycol monophenyl ether, ethylene glycol mono-2-ethylbutyl ether, ethylene glycol dibutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol diethyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol di-n-butyl ether, diethylene glycol mono-n-hexyl ether, ethoxytriglycol, tetraethylene glycol di-n-butyl ether, propylene glycol monomethyl ether (PG ME), propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, anisole, diethyl carbonate, methyl acetate, ethyl acetate, γ-butyrolactone, γ-valerolactone, n-propyl acetate, i-propyl acetate, n-butyl acetate (normal butyl acetate, nBA), i-butyl acetate, sec-butyl acetate, n-pentyl acetate, sec-pentyl acetate, 3-methoxybutyl acetate, methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, benzyl acetate, cyclohexyl acetate, methylcyclohexyl acetate, n-nonyl acetate, methyl acetoacetate, ethyl acetoacetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether acetate,Diethylene glycol monoethyl ether acetate, diethylene glycol mono-n-butyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether acetate, glycol diacetate, methoxytriglycol acetate, ethyl propionate, n-butyl propionate, i-amyl propionate, diethyl oxalate, di-n-butyl oxalate, methyl lactate, ethyl lactate (EL), n-butyl lactate, n-amyl lactate Mil, diethyl malonate, dimethyl phthalate, diethyl phthalate, propylene glycol 1-monomethyl ether 2-acetate (PGMEA), propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropionamide, N-methylpyrrolidone, dimethyl sulfide, diethyl sulfide, thiophene, tetrahydrothiophene, dimethyl sulfoxide, sulfolane, and 1,3-propane sultone. These solvents can be used alone or in combination of two or more. In a preferred embodiment of the present invention, the (B) solvent consists essentially of a solvent selected from the above specific examples, although it is permissible for the (B) solvent to contain a small amount of a solvent for dissolving the solid components of the surfactant or additives.
[0033] The (B) solvent is preferably PGMEA, PGME, anisole, EL, nBA, DBE, or a mixture of any of these, more preferably PGMEA, PGME, or a mixture of these, and even more preferably PGMEA. When two types are mixed, the mass ratio of the first solvent to the second solvent is preferably 95:5 to 5:95 (more preferably 90:10 to 10:90, and even more preferably 80:20 to 20:80).
[0034] In relation to other layers or films, it is also one embodiment that the (B) solvent does not substantially contain water. For example, the amount of water in the (B) solvent as a whole is preferably 0.1 mass% or less, more preferably 0.01 mass% or less, and even more preferably 0.001 mass% or less. It is also a suitable embodiment that the (B) solvent does not contain water (0 mass%).
[0035] (i) Based on the composition, the amount of the solvent (B) is preferably 60 to 98 mass %, more preferably 60 to 95 mass %, still more preferably 70 to 95 mass %, and even more preferably 70 to 90 mass %.
[0036] (C) Surfactant The composition (i) according to the present invention may further comprise a surfactant (C). By including a surfactant, the coating properties can be improved. In the present invention, the (C) surfactant refers to the compound itself having the above-mentioned function. The compound may be dissolved or dispersed in a solvent and contained in the composition, but it is preferable that such a solvent is contained in the composition as the (B) solvent or other components. Hereinafter, the same applies to various additives that may be contained in the composition. Surfactants that can be used in the present invention include (I) anionic surfactants, (II) cationic surfactants, and (III) nonionic surfactants. More specifically, (I) alkylsulfonates, alkylbenzenesulfonic acids, and alkylbenzenesulfonates, (II) laurylpyridinium chloride and laurylmethylammonium chloride, and (III) polyoxyethylene octyl ether, polyoxyethylene lauryl ether, and polyoxyethylene acetylenic glycol ether, fluorine-containing surfactants such as Fluorad (Sumitomo 3M), Megafac (DIC), Sulfuron (Asahi Glass), or organosiloxane surfactants (e.g., KP341, Shin-Etsu Chemical Co., Ltd.) are preferred.
[0037] Based on the (A) hydrocarbon-containing compound, the (C) surfactant is preferably 0.01 to 10 mass %, more preferably 0.05 to 10 mass %, even more preferably 0.05 to 5 mass %, and even more preferably 0.05 to 1 mass %.
[0038] (D) Additives The composition (i) according to the present invention may further contain an additive (D). The additive (D) is a component different from (A), (B) and (C). Preferably, the additive (D) comprises a crosslinking agent, a high carbon material, an acid generator, a radical generator, a photopolymerization initiator, a substrate adhesion enhancer or a mixture thereof. More preferably, the additive (D) comprises a crosslinking agent, an acid generator, a radical generator, a photopolymerization initiator, a substrate adhesion enhancer or a mixture thereof. A more preferred additive (D) is a crosslinking agent. In another embodiment of the present invention, the additive (D) is a high carbon material.
[0039] The crosslinking agent is useful for purposes such as improving the film-forming properties when forming the hydrocarbon-containing film of the present invention, eliminating intermixing with an overlying film (e.g., a silicon-containing intermediate layer and a resist), and eliminating diffusion of low molecular weight components into the overlying film.
[0040] Examples of the crosslinking agent include melamine compounds, guanamine compounds, glycoluril compounds or urea compounds substituted with at least one group selected from methylol groups, alkoxymethyl groups, and acyloxymethyl groups, epoxy compounds, thioepoxy compounds, isocyanate compounds, azide compounds, and compounds containing double bonds such as alkenyl ether groups. These may be used as additives, or may be introduced as pendant groups into the polymer side chain. Compounds containing hydroxyl groups are also used as crosslinking agents. Among the various compounds, examples of epoxy compounds include tris(2,3-epoxypropyl)isocyanurate, trimethylolmethane triglycidyl ether, trimethylolpropane triglycidyl ether, triethylolethane triglycidyl ether, etc. Specific examples of melamine compounds include hexamethylolmelamine, hexamethoxymethylmelamine, compounds in which 1 to 6 methylol groups of hexamethylolmelamine are methoxymethylated and mixtures thereof, hexamethoxyethylmelamine, hexaacyloxymethylmelamine, compounds in which 1 to 6 methylol groups of hexamethylolmelamine are acyloxymethylated and mixtures thereof. Examples of the guanamine compound include tetramethylol guanamine, tetramethoxymethyl guanamine, a compound in which 1 to 4 methylol groups of tetramethylol guanamine are methoxymethylated, and a mixture thereof, tetramethoxyethyl guanamine, tetraacyloxyguanamine, a compound in which 1 to 4 methylol groups of tetramethylol guanamine are acyloxymethylated, and a mixture thereof. Examples of the glycoluril compound include tetramethylol glycoluril, tetramethoxy glycoluril, tetramethoxymethyl glycoluril, a compound in which 1 to 4 methylol groups of tetramethylol glycoluril are methoxymethylated, or a mixture thereof, and a compound in which 1 to 4 methylol groups of tetramethylol glycoluril are acyloxymethylated, or a mixture thereof. Examples of the urea compound include tetramethylol urea, tetramethoxymethyl urea, a compound in which 1 to 4 methylol groups of tetramethylol urea are methoxymethylated, or a mixture thereof, and tetramethoxyethyl urea. Examples of compounds containing an alkenyl ether group include ethylene glycol divinyl ether, triethylene glycol divinyl ether, 1,2-propanediol divinyl ether, 1,4-butanediol divinyl ether, tetramethylene glycol divinyl ether, neopentyl glycol divinyl ether, trimethylolpropane trivinyl ether, hexanediol divinyl ether, 1,4-cyclohexanediol divinyl ether, pentaerythritol trivinyl ether, pentaerythritol tetravinyl ether, sorbitol tetravinyl ether, sorbitol pentavinyl ether, and trimethylolpropane trivinyl ether. The molecular weight of the crosslinking agent is preferably 100-480, more preferably 200-400, and further preferably 300-380.
[0041] Although not intended to limit the present invention, specific examples of crosslinking agents include the following: [ka]
[0042] The high-carbon material is a molecule containing many carbon atoms per molecule, and is a solid component that remains in the hydrocarbon-containing film according to the present invention. By adding the high-carbon material, it is possible to improve the etch resistance. It is not necessary for the high-carbon material itself to be capable of forming a film, but it is sufficient that the high-carbon material can form a hydrocarbon-containing film together with the (A) hydrocarbon-containing compound.
[0043] Although not intended to limit the present invention, specific examples of high carbon materials include isoviolanthrone, 2,7-di(1-pyrenyl)-9,9'-spirobi[9H-fluorene], 9,9-bis[4-[di(2-naphthyl)amino]phenyl]fluorene, 9,9-bis[4-[N-(1-naphthyl)anilino]phenyl]fluorene, 3,4,9,10-perylenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic diimide, benzanthrone, perylene, coronene, 5,12-naphthacenequinone, 6,13-pentacenedione, and fullerene C. 60, C 60 MC 12 (C 60 Condensation N-methylpyrrolidine-mC 12 -phenyl), ICBA(indene-C 60 bisadduct), N,2-diphenyl
[60] fulleropyrrolidine, PCBM (Phenyl-C 61 -Butyric-Acid-Methyl Ester), PCBB(Phenyl-C 61 -Butyric-Acid-Butyl Ester, N-phenyl-2-hexyl
[60] fulleropyrrolidine, and the like.
[0044] In the present invention, based on the (A) hydrocarbon-containing compound, the (D) additive is preferably 0.05 to 100 mass%; more preferably 0.05 to 25 mass%; even more preferably 0.05 to 20 mass%; still more preferably 0.05 to 15 mass%; and even more preferably 0.05 to 10 mass%.
[0045] Manufacturing method of the cured film The method for producing a cured film according to the present invention comprises the following steps. (1) applying (i) a composition over a substrate; (2) forming a hydrocarbon-containing film from the (i) composition; and (3) irradiating the hydrocarbon-containing film with plasma, electron beam and / or ions to form a cured film.
[0046] In the present invention, the method of applying the (i) composition includes coating methods such as spinners and coaters. The (i) composition according to the present invention is advantageous for embedding in a pattern on a substrate. Although it is preferable that the (i) composition is directly in contact with the substrate above the substrate, it may be applied via another film. (i) Methods for forming a hydrocarbon-containing film from the composition include ultraviolet irradiation and / or heating, and preferably include heating.
[0047] Preferably, the ultraviolet irradiation conditions are ultraviolet light having a wavelength of 10 to 380 nm (more preferably 10 to 200 nm) at 100 to 10,000 mJ / cm 2The integrated irradiation amount is irradiated with light.
[0048] Air is suitable as the atmosphere for ultraviolet irradiation and heating. The oxygen concentration can be reduced to prevent oxidation of the composition (i) and / or the hydrocarbon-containing film of the present invention. For example, the oxygen concentration can be reduced to 1,000 ppm or less (preferably 100 ppm or less) by injecting an inert gas (N2, Ar, He or a mixture thereof) into the atmosphere.
[0049] When forming a hydrocarbon-containing film by heating, the heating conditions are appropriately selected from the range of a heating temperature of 80 to 800°C (preferably 200 to 700°C, more preferably 300 to 600°C) and a heating time of 30 to 180 seconds (preferably 30 to 120 seconds). Without being bound by theory, it is believed that high-temperature heating can effectively promote crosslinking by groups that crosslink polymers with each other, such as ethynyl groups, and contribute to densifying the cured film. Heating can be performed in multiple steps (step baking). A hydrocarbon-containing film can be formed by heating alone, but a combination with ultraviolet irradiation is also suitable.
[0050] The hydrocarbon-containing film is irradiated with plasma, electron beams, and / or ions to form a hardened film. Without being bound by theory, it is believed that the exposure causes the chemical bonds in the hydrocarbon-containing film to dissociate and recombine, reconstructing the film into a hardened film having a diamond-like carbon structure, thereby contributing to an increase in hardness and density. One embodiment of the present invention includes (i) forming a cured film by irradiating the composition with plasma, electron beams, and / or ions immediately after coating the composition. In other words, the present invention also includes an embodiment in which the above steps (2) and (3) proceed almost simultaneously in a single operation (step).
[0051] The plasma irradiation can be performed by a known method, for example, the method described in Japanese Patent No. 5746670 (patent document) and "Improvement of the wiggling profile of spin-on carbon hard mask by H2 plasma treatment" (J. Vac. Sci. Technol. B 26(1), Jan / Feb 2008, p67-71, non-patent document). The RF discharge power can be selected from the range of 1,000 to 10,000 W, and 1,000 to 5,000 W is more preferable. The gas atmosphere may include N2, NF3, H2, rare gas, and fluorocarbon; preferably, Ar, Ne, NF3, H2, CF4, CHF3, CH2F2, CH3F, C4F6, and C4F8. Two or more of these gases may be mixed. The advantage of the present invention is that the effect of the present invention can be expected even when a gas atmosphere that does not contain O2 is used. The time can be selected from 10 to 240 seconds. The pressure can be selected appropriately.
[0052] The electron beam irradiation can be performed by a known method, for example, the method described in "Technology and Use of Electron Beam Irradiation Apparatus" (SEI Technical Review, Vol. 181, p. 50-57, July 2012, non-patent document). The accelerating voltage can be selected from the range of 2 to 200 kV. The irradiation dose can be selected from 100 to 5,000 kGy. The electron beam irradiation is preferably carried out while heating the material, and the temperature can be selected from the range of 80 to 800° C. (preferably 200 to 700° C., and more preferably 300 to 600° C.). Ion irradiation can be performed by a known method. For example, the method described in "Raman spectroscopy and microhardness of ion-implanted aC:H-films" (Ceramics Int. 26(1), 2000, p29-32, non-patent literature) can be used. A preferred embodiment of ion irradiation in the present invention is ion implantation. The elemental species of the ions to be irradiated include hydrogen, boron, carbon, nitrogen, and rare gases, preferably boron, carbon, nitrogen, neon, argon, etc., and more preferably carbon, nitrogen, etc. Two or more of these gases may be mixed for use. The acceleration voltage can be selected from the range of 3 to 1000 kV, more preferably 5 to 750 kV, and even more preferably 10 to 500 kV. The exposure dose is 10 13 ~10 18 ion / cm 2 The irradiation dose can be selected from 5×10 13 ~5×10 17 ion / cm 2 and more preferably 10 14 ~10 17 ion / cm 2 It is. Ion irradiation can also be performed while heating the inside of the device chamber. In this case, the temperature can be selected to be 500°C or less. When heating is performed after plasma irradiation and electron beam irradiation, the heating conditions are appropriately selected from the range of a heating temperature of 80 to 800°C (preferably 200 to 700°C, more preferably 300 to 600°C) and a heating time of 30 to 180 seconds (preferably 30 to 120 seconds). Without being bound by theory, it is believed that high-temperature heating after plasma and electron beam irradiation can bond dangling bonds and contribute to densifying the cured film.
[0053] As the irradiation device, Tactras Vigus, EB-ENGINE (Hamamatsu Photonics), and EXCEED2300AH (Nissin Ion Equipment) can be used. It is possible to select the device and set the conditions so as to obtain the effects of the present invention.
[0054] As one embodiment of the present invention, the cured film formed in the step (3) can have an advantageous effect of increasing the film density by 5 to 75% and / or increasing the film hardness by 50 to 500% compared to the hydrocarbon-containing film formed in the step (2). In addition, the intensity ratio R of the G band to the D band in Raman spectroscopy (measured at a laser wavelength of 514.5 nm) of the cured film formed in step (3) was D / I G can be 0.35 to 0.90, and, without being bound by theory, it is believed that it is possible for the carbon to have a diamond-like carbon structure. In addition, it is believed that the hydrocarbon-containing film formed in step (2) is more easily etched by 5 to 200% (preferably 5 to 100%, more preferably 5 to 50%, and even more preferably 10 to 50%) than the cured film formed in step (3) (the latter cured film has higher etching resistance). Preferably, the surface resistivity of the cured film formed in step (3) is 10 9 ~10 16 Ω□ (preferably 10 12 ~10 16 Ω□, more preferably 10 13 ~10 16 That is, the (A) hydrocarbon-containing compound is not a conductive polymer precursor, and the cured film according to the present invention is not a conductive polymer film.
[0055] In one aspect of the present invention, there is provided a carbon-containing cured film having the following characteristics: Film density is 1.3 to 3.2 g / cm 3 ; A film hardness of 1.5 to 20 GPa; and / or Intensity ratio R = I between G band and D band in Raman spectroscopy (laser wavelength 514.5 nm measurement) D / I G is 0.35~0.90. Preferably, the carbon-containing cured film is formed by plasma, electron beam and / or ion irradiation. More preferably, the film has a surface resistivity of 10 9 ~10 16 In a more preferred embodiment of the present invention, the composition (i) is used as the composition for forming such a carbon-containing cured film.
[0056] The film known as SOC is described in “The Role of Underlayers in EUVL” (Journal of Photopolymer Science and Technology Vol.31, Number 2, p209-214, 2018), but its film density is 1.05-1.32g / cm 3 It was only to an extent. The cured film or carbon-containing cured film according to the present invention preferably has a film density of 1.3 to 3.2 g / cm. 3 (More preferably 1.4 to 3.2 g / cm 3 , and more preferably 1.5 to 2.8 g / cm 3 It is believed that the high film density of the cured film contributes to the increase in etch resistance. Also, if the stress of the cured film is too strong, it is believed to be disadvantageous because it puts stress on the substrate. The film density can be measured by using, for example, the method described in the Examples, and can be adjusted by appropriately combining this with a known method.
[0057] The film according to the present invention preferably has a film hardness of 1.5 to 20 GPa (more preferably 1.7 GPa to 20 GPa, even more preferably 2.0 GPa to 15 GPa, and even more preferably 2.0 GPa to 10 GPa). The film hardness can be measured, for example, by the method described in the Examples, and can be adjusted by appropriately combining this with a known method.
[0058] The film according to the present invention preferably has an intensity ratio R=ID / IG of G band to D band in Raman spectroscopy (measured at a laser wavelength of 514.5 nm) of 0.35 to 0.90 (more preferably 0.40 to 0.90, even more preferably 0.40 to 0.80, and still more preferably 0.45 to 0.70). For the Raman spectroscopic analysis, for example, the method described in the Examples can be used, and this can be appropriately combined with a known method (for example, Japanese Patent No. 3914179 (Patent Document)) for adjustment.
[0059] <Method of manufacturing resist film and resist pattern> It is also possible to produce a resist film on the cured film produced by the method according to the present invention. The method for producing a resist film according to the present invention includes the steps of: (4) applying a resist composition over the cured film; (5) heating the resist composition to form a resist layer; The present invention relates to a method for producing a semiconductor device comprising the steps of: Furthermore, the present invention also makes it possible to produce a resist pattern from the resist film. (6) exposing the resist layer; Optionally, (7) post-exposure baking the resist layer; and (8) Developing the resist layer. The present invention relates to a method for producing a semiconductor device comprising the steps of: For clarity, the numbers in parentheses indicate the order, e.g., step (4) is performed before step (5).
[0060] An embodiment of the method for producing a resist film and a resist pattern according to the present invention will now be described. The resist composition is applied above a substrate (e.g., a silicon / silicon dioxide-coated substrate, a silicon nitride substrate, a silicon wafer substrate, a glass substrate, an ITO substrate, etc.) by a suitable method. Here, in the present invention, above includes the case where the resist composition is formed directly above the substrate and the case where the resist composition is formed through another layer. For example, a planarizing film or a resist underlayer film may be formed directly above the substrate, and the resist composition may be applied directly above the planarizing film or resist underlayer film. The application method is not particularly limited, and examples thereof include a method of application using a spinner or a coater. After application, a resist layer is formed by heating. The heating in (5) is performed, for example, using a hot plate. The heating temperature is preferably 60 to 140°C, more preferably 90 to 110°C. The temperature here refers to the heating atmosphere, for example, the heating surface temperature of a hot plate. The heating time is preferably 30 to 900 seconds, more preferably 60 to 300 seconds. The heating is preferably performed in air or nitrogen gas atmosphere.
[0061] The thickness of the resist layer is selected according to the purpose. The thickness of the resist layer can be made larger than 1 μm.
[0062] The resist layer is exposed through a predetermined mask. The wavelength of light used for exposure is not particularly limited, but exposure with light having a wavelength of 190 to 440 nm is preferred (more preferably 240 to 370 nm). Specifically, KrF excimer laser (wavelength 248 nm), ArF excimer laser (wavelength 193 nm), i-line (wavelength 365 nm), h-line (wavelength 405 nm), g-line (436 nm), etc. can be used. The wavelength is more preferably 240 to 440 nm, even more preferably 360 to 440 nm, and even more preferably 365 nm. These wavelengths are allowed to have a range of ±1%.
[0063] After exposure, a post exposure bake (hereinafter sometimes referred to as PEB) may be optionally performed. The heating in (7) is performed, for example, by using a hot plate. The temperature of the post exposure bake is preferably 80 to 160°C, more preferably 105 to 115°C, and the heating time is 30 to 600 seconds, preferably 60 to 200 seconds. The heating is preferably performed in air or nitrogen gas atmosphere.
[0064] After PEB, development is carried out using a developer. As the development method, a method conventionally used for developing photoresists, such as a paddle development method, an immersion development method, and a swing immersion development method, can be used. As the developer, an aqueous solution containing an inorganic alkali such as sodium hydroxide, potassium hydroxide, sodium carbonate, or sodium silicate, an organic amine such as ammonia, ethylamine, propylamine, diethylamine, diethylaminoethanol, or triethylamine, or a quaternary amine such as tetramethylammonium hydroxide (TMAH), is used, and preferably a 2.38 mass % TMAH aqueous solution. A surfactant can also be added to the developer. The temperature of the developer is preferably 5 to 50°C, more preferably 25 to 40°C, and the development time is preferably 10 to 300 seconds, more preferably 30 to 60 seconds. After development, washing with water or a rinsing treatment can be performed as necessary.
[0065] As an embodiment of the present invention, the produced resist pattern can be used as a mask to pattern various substrates that serve as the base. The substrate can be processed directly using the resist pattern as a mask, or can be processed via an intermediate layer. For example, the resist underlayer film can be patterned using the resist pattern as a mask, and the substrate can be patterned using the resist underlayer film pattern as a mask. For processing, a known method can be used, such as a dry etching method, a wet etching method, an ion implantation method, or a metal plating method. It is also possible to wire electrodes, etc., on the patterned substrate.
[0066] substrate In the present invention, examples of the substrate include semiconductor wafers, glass substrates for liquid crystal display devices, glass substrates for organic EL display devices, glass substrates for plasma displays, substrates for optical discs, substrates for magnetic discs, substrates for magneto-optical discs, glass substrates for photomasks, substrates for solar cells, and the like. The substrate may be an unprocessed substrate (e.g., a bare wafer) or a substrate to be processed (e.g., a patterned substrate). The substrate may be composed of a plurality of layers laminated. Preferably, the surface of the substrate is a semiconductor. The semiconductor may be composed of any of oxides, nitrides, metals, or any combination thereof. Also, preferably, the surface of the substrate is selected from the group consisting of Si, Ge, SiGe, Si3N4, TaN, SiO2, TiO2, Al2O3, SiON, HfO2, T2O5, HfSiO4, Y2O3, GaN, TiN, TaN, Si3N4, NbN, Cu, Ta, W, Hf, and Al.
[0067] device Devices can be manufactured by further processing the substrate according to the present invention. Examples of the device include semiconductor elements, liquid crystal display elements, organic EL display elements, plasma display elements, and solar cell elements. The device is preferably a semiconductor. Known methods can be used for these processes. After device formation, if necessary, the substrate can be cut into chips, connected to a lead frame, and packaged with resin. An example of this packaged product is a semiconductor.
[0068] The present invention will be described with examples as follows. Note that the aspects of the present invention are not limited to these examples.
[0069] <Synthesis of P0> Prepare a reactor equipped with a stirrer, Liebig condenser, heating device, nitrogen inlet tube and temperature control device. Add 9-fluorenone (200 parts, Tokyo Chemical Industry Co., Ltd.), 9,9-bis(4-hydroxyphenyl)fluorene (2333 parts, Osaka Gas Chemical Co., Ltd.) and dichloromethane (10430 parts) to the reactor, and maintain the temperature at 40°C while stirring under a nitrogen atmosphere. Then, slowly add trifluoromethanesulfonic acid (92 parts, Mitsubishi Materials Electronics Co., Ltd.) and 3-mercaptopropionic acid (6 parts, Tokyo Chemical Industry Co., Ltd.) dissolved in dichloromethane (200 parts) to the reactor, and keep the temperature at 40°C while stirring and reacting for 4 hours. After the reaction is completed, return the solution to room temperature, add water to the reaction solution, remove excess 9,9-bis(4-hydroxyphenyl)fluorene by filtration, and wash with dichloromethane. Wash the dichloromethane solution thoroughly with water to remove trifluoromethanesulfonic acid. Thereafter, dichloromethane is distilled off at 40°C and 10 mmHg to obtain P0 (2111 parts). The molecular weight is measured by GPC (tetrahydrofuran) to find that the number average molecular weight Mn is 533 Da, the weight average molecular weight Mw is 674 Da, and the molecular weight distribution (Mw / Mn) is 1.26.
[0070] <Synthesis Example 1: Synthesis of P1> A reactor equipped with a stirrer, Liebig condenser, heating device, nitrogen inlet tube and temperature control device is prepared. P0 (350 parts), potassium carbonate (562 parts) and acetone (1414 parts) are added to the reactor, and the temperature is maintained at 56°C while stirring under a nitrogen atmosphere. Allyl bromide (500 parts, Tokyo Chemical Industry) is then slowly added to the reactor, and the temperature is maintained at 56°C while stirring and reacting for 3 hours. After the reaction is completed, the solution is returned to room temperature, the excess potassium carbonate and salt are removed by filtration, and the precipitate is washed with acetone. Then, the acetone is distilled off at 40°C and 10 mmHg. The obtained solid is dissolved in ethyl acetate (3000 parts), and the ethyl acetate solution is thoroughly washed with water to remove metal impurities. After distilling off the ethyl acetate at 40°C and 10 mmHg, the obtained solid is dissolved in acetone (600 parts). The acetone solution is then added to n-heptane (6000 parts), the solid matter is filtered, and dried at 100°C and 10 mmHg to obtain P1 (345 parts). The molecular weight is measured by GPC (tetrahydrofuran) to find that the number average molecular weight Mn is 671 Da, the weight average molecular weight Mw is 833 Da, and the molecular weight distribution (Mw / Mn) is 1.32. [ka]
[0071] <Synthesis Example 2: Synthesis of P2> A reactor equipped with a stirrer, Liebig condenser, heating device, nitrogen inlet tube, and temperature control device is prepared. P0 (200 parts), potassium carbonate (323 parts), and acetone (616 parts) are added to the reactor, and the temperature is maintained at 56°C while stirring under a nitrogen atmosphere. Then, 3-bromo-1-propyne (278 parts) is slowly added to the reactor, and the temperature is maintained at 56°C while stirring and reacting for 3 hours. After the reaction is completed, the solution is returned to room temperature, and excess potassium carbonate and salts are removed by filtration, and the precipitate is washed with acetone. Then, acetone is distilled off at 40°C and 10 mmHg. The obtained solid is dissolved in ethyl acetate (820 parts), and the ethyl acetate solution is thoroughly washed with water to remove metal impurities. After distilling off the ethyl acetate at 40°C and 10 mmHg, the obtained solid (185 parts) is dissolved in acetone (185 parts). Methanol (1850 parts) is then added to the acetone solution, the solids are filtered, and dried at 100°C and 10 mmHg to give P2 (76 parts). The molecular weight is measured by GPC (tetrahydrofuran) to find Mn=789 Da, Mw=1,054 Da, and Mw / Mn=1.34. [ka]
[0072] Preparation Example 1 of Composition 1 Add P1 (13.9 parts) and Megafac R-41 (0.1 parts, DIC) to propylene glycol 1-monomethyl ether 2-acetate (PGMEA) (86 parts) and stir at room temperature for 1 hour. Check visually that the solute is completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter (Merck Millipore, SLFG025NS) to obtain composition 1.
[0073] Preparation Example 2 of Composition 2 Add P2 (11.9 parts) and Megafac R-41 (0.1 parts) to PGMEA (88 parts) and stir at room temperature for 1 hour. Check visually that the solute is completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter to obtain composition 2.
[0074] Preparation Example 3 of Composition 3 Add P3 (13.9 parts) and Megafac R-41 (0.1 parts) of the structure shown below to PGMEA (86 parts) and stir at room temperature for 1 hour. Visually confirm that the solute is completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter to obtain composition 3. [ka]
[0075] Preparation Example 4 of Composition 4 Add P4 (14.9 parts) and Megafac R-41 (0.1 parts) of the structure shown below to PGMEA (85 parts) and stir at room temperature for 1 hour. Visually confirm that the solute is completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter to obtain composition 4. [ka]
[0076] Preparation Example 5 of Composition 5 Add P5 (14.9 parts) and Megafac R-41 (0.1 parts) of the structure shown below to PGMEA (85 parts) and stir at room temperature for 1 hour. Visually confirm that the solute is completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter to obtain composition 5. [ka]
[0077] Preparation Example 6 of Composition 6 Add P6 (13.9 parts) and Megafac R-41 (0.1 parts) of the structure shown below to PGMEA (86 parts) and stir at room temperature for 1 hour. Visually confirm that the solute is completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter to obtain composition 6. [ka]
[0078] Preparation Example 7 of Composition 7 Add the above-mentioned P0 (24.9 parts) and Megafac R-41 (0.1 parts) to PGMEA (75 parts) and stir at room temperature for 1 hour. Check visually that the solute is completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter to obtain composition 7.
[0079] Preparation Example 8 of Composition 8 Add P7 (12.9 parts), P8 (1 part), and Megafac R-41 (0.1 parts) to PGMEA (87 parts) and stir at room temperature for 1 hour. Check visually that the solute is completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter to obtain composition 8. [ka] [ka]
[0080] Preparation Example 9 of Composition 9 Add P2 (8.9 parts), P9 (5 parts) whose structure is shown below, and Megafac R-41 (0.1 parts) to PGMEA (85 parts) and stir at room temperature for 1 hour. Visually check to ensure that the solutes are completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter to obtain composition 9. [ka]
[0081] Preparation Example 10 of Composition 10 Add P2 (2.9 parts) and Megafac R-41 (0.1 parts) to PGMEA (97 parts) and stir at room temperature for 1 hour. Check visually that the solute is completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter to obtain composition 10.
[0082] Preparation Example 11 of Composition 11 Add P2 (3.9 parts) and Megafac R-41 (0.1 parts) to PGMEA (96 parts) and stir at room temperature for 1 hour. Check visually that the solute is completely dissolved. The mixture is filtered through a 0.2 μm fluororesin filter to obtain composition 11.
[0083] Formation of Hydrocarbon-Containing Films Each composition is applied to a bare silicon wafer at 1,500 rpm using a CLEAN TRACK ACT 12 (Tokyo Electron). The wafer is baked at 250°C for 60 seconds in an air atmosphere, and then baked at 450°C for 120 seconds in a nitrogen atmosphere. A hydrocarbon-containing film is obtained from the composition.
[0084] Formation of hardened film (in the case of plasma treatment) The wafer on which the above-mentioned hydrocarbon-containing film is formed is subjected to plasma treatment for 2 minutes using Tactras Vigus (Tokyo Electron).
[0085] Formation of hardened film (in the case of electron beam treatment) The wafer on which the above-mentioned hydrocarbon-containing film is formed is irradiated with 1 MGy electron beams while being heated to 400° C. by EB-ENGINE (Hamamatsu Photonics).
[0086] Formation of hardened film (in the case of ion irradiation treatment) The wafer on which the above-mentioned hydrocarbon-containing film was formed was subjected to 10 s of acceleration voltage of 10 kV. 16 ion / cm 2 The carbon ion irradiation is performed.
[0087] Film thickness measurement A wafer cross section is prepared, an SEM photograph is taken using a JSM-7100F (JEOL), and the film thickness is measured.
[0088] Measuring film density Using a fully automated multipurpose X-ray diffraction system SmartLab (Rigaku), high-resolution X-ray reflectivity measurement was performed with a target cathode of Cu, output of 45 kV × 200 mA, analysis range of 0.2 to 3.0°, and measurement step of 0.002°. The film density was calculated by fitting the simulation curve to the obtained X-ray reflectivity curve.
[0089] Measuring film hardness Using an ENT-2100 indentation hardness tester (Elionix), the film hardness is calculated with an indentation load of 10 μN, 100 measurements, and a step interval of 100 ms.
[0090] I D / I G Measurement A triple-laser Raman spectrometer, RAMANOR T64000 (HORIBA Jobin Yvon), was used for Raman spectroscopy at a laser wavelength of 514.5 nm. D / I G Measure. Approximately 900~1800cm -1 The broad peak at 1590 cm was calculated using a Gaussian function. -1 G band and 1350 cm -1 Nearby D band, 1100 cm -1 The intensity of the D band and the G band are calculated by dividing the band into three. D / I G Calculate.
[0091] Etching resistance measurement Using an etching system NE-5000N (ULVAC), dry etching is performed with a chamber pressure of 0.17 mT, RF power of 200 W, gas flow rates of CF4 (50 sccm), Ar (35 sccm), and O2 (4 sccm) for 30 seconds. The film thickness before and after etching is measured as described above in "Film Thickness Measurement", and the difference between the former and latter is obtained to calculate the amount of film thickness reduction per unit time.
[0092] Evaluation results The evaluation results are shown in Table 1 below. [Table 1] In the above table, For compositions 1 to 9, "before treatment" refers to the results of evaluating the hydrocarbon-containing film before plasma treatment, and "after treatment" refers to the results of evaluating the cured film after plasma treatment. For Composition 10, "before treatment" refers to the results evaluating the hydrocarbon-containing film before electron beam irradiation, and "after treatment" refers to the results evaluating the cured film after electron beam irradiation. For Composition 11, "before treatment" refers to the results of evaluating the hydrocarbon-containing film before ion irradiation, and "after treatment" refers to the results of evaluating the cured film after ion beam irradiation.
[0093] Comparative Example, Evaluation of Etching Resistance of Hydrocarbon-Containing Film The etching resistance of the hydrocarbon-containing film of composition 2 before the plasma treatment is measured in the same manner as above. The etching resistance is 204 nm / min. Comparing the etching resistance of the hydrocarbon-containing film obtained from composition 2 (before plasma treatment) and the cured film (after plasma treatment), the former is about 24% more susceptible to etching.
Claims
1. A method for producing a cured film, comprising the steps of: (1) applying (i) a composition over a substrate; (2)(i) forming a hydrocarbon-containing film from the composition; and (3) Irradiating the hydrocarbon-containing film with an electron beam or ions to form a cured film; provided that (i) the composition comprises (A) a hydrocarbon-containing compound, and (B) a solvent; The (A) hydrocarbon-containing compound comprises a structural unit (A1) represented by the following formula (A1): 【Chemistry 1】 Here, Ar 11 is R 11 C substituted or unsubstituted 6-60 (where Ar is a hydrocarbon) 11 does not contain a condensed aromatic ring); R 11 is C 1-20 linear, branched or cyclic alkyl, amino, or alkylamino; R 12 is I, Br or CN; p 11 is a number from 0 to 5, and p 12 is a number between 0 and 1, and q 11 is a number from 0 to 5, and q 12 is a number between 0 and 1, and r 11 is a number from 0 to 5, and s 11 is a number from 0 to 5; p 11 , q 11 and r 11 cannot be zero simultaneously within one unit, When electron beam irradiation is performed in step (3), Acceleration voltage is 2 kV to 200 kV, or The irradiation dose is 100 kGy to 5,000 kGy. When ions are irradiated in the step (3), The elemental species of the ions to be irradiated is hydrogen, boron, carbon, nitrogen, a rare gas, or a mixture of any of these, Acceleration voltage is 3 to 1000 kV, or The irradiation dose is 10 13 ~10 18 ions / cm 2 It is.
2. The method for producing a cured film according to claim 1, wherein the formula (A1) is the following formula (A1-1) or (A1-3): 【Chemistry 2】 Ar 21 is C 6-50 is an aromatic hydrocarbon of R 21 , R 22 and R 23 are each independently C 6-50 is a single bond that connects the aromatic hydrocarbon, hydrogen, or other unit of n 21 is an integer of 0 or 1; Here, Ar 21 , R 21 , R 22 and R 23 does not contain a condensed aromatic ring, R 12 , p 11 , p 12 , q 11 , q 12 , r 11 and s 11 are each independently defined as above; 【Chemistry 3】 Ar 41 is C 6-50 is an aromatic hydrocarbon of R 41 and R 42 are each independently C 1-10 alkyl, R 41 and R 42 may form a hydrocarbon ring, * The carbon atom at position 41 is a quaternary carbon atom, L 41 is C 6-50 is a single bond that connects to an arylene or other structural unit of Here, R 12 , p 11 , p 12 , q 11 , q 12 , r 11 and s 11 are each independently defined as above; Preferably, the molecular weight of (A) the hydrocarbon-containing compound is from 500 to 6,000.
3. (i) the method for producing a cured film according to claim 1 or 2, wherein the composition further comprises (C) a surfactant or (D) an additive; The additive (D) includes a crosslinking agent, a high carbon material, an acid generator, a radical generator, a photopolymerization initiator, a substrate adhesion enhancer, or a mixture thereof.
4. The method for producing a cured film according to any one of claims 1 to 3, wherein (B) the solvent comprises an organic solvent; Here, the organic solvent comprises a hydrocarbon solvent, an ether solvent, an ester solvent, an alcohol solvent, a ketone solvent, or a mixture thereof.
5. (i) the content of the hydrocarbon-containing compound (A) is 2 to 30 mass % based on the composition; (i) the content of the solvent (B) is 60 to 98 mass% based on the composition; The content of the surfactant (C) is 0.01 to 10 mass % based on the hydrocarbon-containing compound (A), or The method for producing a cured film according to any one of claims 1 to 4, wherein the content of the additive (D) is 0.05 to 100 mass% based on the hydrocarbon-containing compound (A).
6. The method for producing a cured film according to any one of claims 1 to 5, characterized in that the (A) hydrocarbon-containing compound is a polymer, and an aldehyde derivative used when synthesizing the polymer is in an amount of 0 to 30 mol % based on the sum of all elements used in the synthesis.
7. The method for producing a cured film according to any one of claims 1 to 6, wherein the cured film formed in the step (3) has a film density increased by 5 to 75% or a film hardness increased by 50 to 500% compared to the hydrocarbon-containing film formed in the step (2).
8. The intensity ratio R of the G band to the D band in Raman spectroscopy (measured at a laser wavelength of 514.5 nm) of the cured film formed in step (3) is R=I D / I G The method for producing a cured film according to any one of claims 1 to 7, wherein the viscosity is 0.35 to 0.
90.
9. the hydrocarbon-containing film formed in step (2) is 5 to 200% more easily etched than the cured film formed in step (3); or The surface resistivity of the cured film formed in step (3) is 10 9 ~10 16 The method for producing the cured film according to any one of claims 1 to 8, wherein the viscosity is Ω□.
10. The method for producing a cured film according to any one of claims 1 to 9, wherein the step of forming a hydrocarbon-containing film from the composition in step (2) (i) comprises heating at 80 to 800°C for 30 to 180 seconds.
11. The method for producing a cured film according to any one of claims 1 to 9, wherein the step of forming a hydrocarbon-containing film from the composition in step (2) (i) comprises irradiating with ultraviolet light of 10 to 380 nm.
12. The film density of the cured film is 1.3 to 3.2 g / cm 3 or The method for producing a cured film according to any one of claims 1 to 11, wherein the cured film has a film hardness of 1.5 to 20 GPa.
13. A method for producing a resist layer above the cured film according to at least one of claims 1 to 12.
14. A method for producing a resist pattern, comprising exposing and developing the resist layer according to claim 13.
15. A method for manufacturing a device, comprising the method according to at least one of claims 1 to 14.
Citation Information
Patent Citations
Brushless linear servo motor
JP1982046670A
Film-forming composition, insulating film and electronic device
JP2008231174A
Method for producing cured film, film, and plasma-initiated polymerizable composition
JP2013177542A
Method for forming resist underlay film and pattern forming method
JP2016206676A
Composition for forming underlayer film for electronic wiring resist and containing lactone-structure-containing polymer
WO2015093323A1